Pembatalan Perkawinan Menurut Hukum Islam dan UU Hukum Keluarga di Negara Muslim: Studi Perbandingan Antara Negara Mesir, Aljazair, Yordan dan Maroko - Sukron Ma’mun (Humaniora, 2014)
The purpose of this paper is to find out the reasons for the cancellation of marriage according to the concept of classical Islamic law and the laws of Muslim countries such as Egypt, al-Jazair, Jordan, and Morocco wich adopted from the concept of Islamic law. Then compare the changes in the state laws from the classical Islamic legal concept. In this paper the author uses descriptive-analytical-comparative method. The data analysis was done by using content analysis method (content analysis), which is an attempt to explore the symbolic meaning of the message or the contents of a book or other writings products.The results showed that the comparison of horizontal four countries mentioned above in its laws, have in common the material, especially the most prominent is reason for cancellation of marriage with disabilities or diseases in one partner. As for the inability make a living only Jordan which did not mention it in the family law legislation.